Examining stealing thunder as a new service recovery strategy: impact on customer loyalty. Issue 2 (18th January 2019) - Guchait, Priyanko; Han, Rachel; Wang, Xingyu; Abbott, JéAnna; Liu, Yetong
Abstract : Purpose: This paper aims to examine how stealing thunder, apology and compensation influence customer loyalty in a service failure context, and how trust mediates these relationships. Design/methodology/approach: The study adopted a scenario-based between-group experimental design involving 300 customers. Findings: The results indicated that stealing thunder, apology and compensation have a joint effect on customer loyalty. Specifically, this study found a significant positive impact of stealing thunder on loyalty; a two-way interaction effect of compensation and stealing thunder on loyalty; and a three-way interaction effect on loyalty. Additionally, trust mediated the relationship between service recovery attributes (stealing thunder, apology and compensation) and customer loyalty. Originality/value: This study introduces a new service recovery method called Stealing Thunder, which is commonly used in the fields of law and communication and is the first to assess stealing thunder as a proactive/preemptive strategy to handle service failures and its impact on customer loyalty. The study found that when stealing thunder was present, compensation had no influence on customer loyalty. Moreover, when stealing thunder was present, compensation had no impact on loyalty when apology was not present. However, compensation had a significant effect on loyalty when stealing thunder and apology were not present. This study finds the value of including proactive/preemptive strategies (stealing thunder) along with regular service recovery strategies (e.g. apology and compensation) in the service recovery process. Results show that service recoveries that include stealing thunder help service failure recovery significantly by increasing customer's trust.